Cavity Enhanced Organic Photodiodes with Charge Collection Narrowing. Issue 8 (17th February 2019) - Yazmaciyan, Aren; Meredith, Paul; Armin, Ardalan
Abstract: Color discrimination in photodetection is conventionally achieved using broadband‐absorbing inorganic semiconductors with passive optical filters. Organic semiconductors show promise to deliver narrowband spectral responses due to their tunable optical properties. While achieving narrow‐absorbing organic semiconductors is an ongoing endeavor in the synthetic chemistry community, charge collection narrowing is introduced as a "material‐agnostic" technique to realize narrowband spectral responses using broadband absorbers such as blends of organic semiconductors, inorganic nanocrystals, and perovskites in a photodiode architecture. Charge collection narrowing in organic semiconductors demands photoactive junction thicknesses on the order of a few micrometers causing fabrication difficulties and limitations in device metrics such as frequency bandwidth. In this work it is shown that electrical inversion can result in charge collection narrowing in organic photodiodes with active layer thicknesses on the order of hundreds of nanometers and hence much easier to achieve via high throughput solution processing techniques. Additionally, it is shown that an indium tin oxide/gold electrode with modified work function acts as a cavity mirror, further narrowing the spectral response and at the same time delivering an extremely selective cathode, suppressing the dark current dramatically. Nearly voltage independent detectivities of 10 13 Jones are achieved with an active sensing area of 0.2 cm 2 . Abstract : Narrowband organic photodiodes that exhibit cavity enhanced charge collection narrowing in junctions thinner than previously realized are reported. These photodetectors possess a state‐of‐the‐art noise equivalent power of nearly 30 fW (at unity bandwidth) and a virtually voltage independent specific detectivity of 10 13 Jones. This is a generic strategy to create narrowband spectral responses in broadband absorbing organic semiconductors.